Facile Fabrication of P(Electrodeposition)/N(Solvothermal) 2D‐WS2‐Homojunction Based High Performance Photo Responsive, Strain Modulated Piezo‐Phototronic Diode. Issue 12 (4th November 2019) - Veeralingam, Sushmitha; Durai, Lignesh; Badhulika, Sushmee
Abstract: In this work, we demonstrate a low cost, cleanroom free fabrication approach of 2D (2‐dimensional) WS2 p‐n homojunction as a piezo phototronic diode. The p‐type WS2 was deposited over the flexible ITO/PET substrate using electrodeposition technique and the n‐type WS2 was synthesized using very simple and cost‐effective solvothermal technique. XRD and Raman studies confirmed the formation of both p‐type and n‐type WS2 with 3R and 2H structure holding the vibration modes of WS2 .To examine the photoresponsive properties the diode was irradiated with visible light and an increase in 12% of the photo current was observed in the reverse bias with the illumination power intensity of 8.25 mW/cm 2 . Further, when the diode was subjected to 0.98% of tensile strain the current was increased up to 91.6%. This enhanced response can be attributed to the piezo‐phototronic effect exhibited by the few layers WS2 structure, which leads to the modulation of the potential at the p‐n junction interface leading to the increase in the carrier concentration of electrons flowing through the device. The p‐n homojunction diode exhibited excellent responsivity and detectivity values of 44.8 A/W and 11.2×10 12 Jones respectively with an illumination intensity of 1.26 mW/cm 2 and with a very low tensile strain of 0.98% which are higher than those of devices fabricated using sophisticated techniques which find numerous applications in flexible‐electronics. Abstract : A 2D (2‐dimensional) WS2 p‐n homojunction was demonstrated as a piezo phototronic diode. An increase in 12% of the photo current was observed in the reverse bias with the illumination power intensity of 8.25 mW/cm 2 . Further, when the diode was subjected to 0.98% of tensile strain the current was increased up to 91.6%. The p‐n homojunction diode exhibited excellent responsivity and detectivity values of 44.8 A/W and 11.2×10 12 Jones respectively.